P Upaya Preventif Untuk Mengurangi Angka Kematian Ibu Akibat Hipertensi dalam Kehamilan - Putu, Ni Putu Ayu Krisna Yuniastuti; I Kadek Adi Paramartha (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2022)
Hypertensive disorders occur 5-10 percent of all pregnancies. Hypertension, especially in pregnancy, is a cause of maternal morbidity and mortality along with bleeding and infection. The purpose of this review article is to find out preventive measures to prevent hypertension in pregnancy.The method used in this article is a literature review through a search on Google Scholar. Results: There are many problems faced by developing countries in improving health services to prevent hypertension in pregnancy, ranging from the lack of health workers, health financing problems to the lack of public awareness, especially pregnant women who do not realize how dangerous hypertension is in pregnancy. It is necessary to improve access to health services in accordance with the integrated health service model, starting from the community, primary health facilities to referral facilities, to be able to detect it early.